Comparison of Arthroscopic to Open Tibiotalocalcaneal Arthrodesis in High-risk Patients. Issue 3 (14th September 2018) - Polzer, Hans; Braunstein, Mareen; Baumbach, Sebastian
Category: Ankle Arthritis Introduction/Purpose: Patients undergoing tibiotalocalcaneal arthrodesis (TTCA) often suffer from co-morbidities increasing complications such as surgical side infections (SSI) and non-unions. High complications rates following open TTCA led to the development of arthroscopic techniques. Aim of this retrospective case-control study was to compare the results of open to arthroscopic TTCA in high-risk patients. Methods: Patient selection was based on the authors' TTCA database. First, patients treated by arthroscopic TTCA (after 07/2013) using a curved intramedullary nail with a follow-up of >= 1 year were selected. Second, patients receiving open TTCA (prior 07/2013), with comparable co-morbidities and retrospectively suitable for arthroscopic TTCA were identified. Both techniques were conducted in a standardized technique with only the surgical approach differing. Primary outcome parameter were complications within a follow-up of 1 year. Eight open and 14 arthroscopic TTCAs (mean age 59±10 years, 91% male) were included. Patient demographics, indications, co-morbidities, and number of previous surgical interventions were similar for both groups. Three patients in the open and 4 in the arthroscopic group suffered from preoperative plantar ulceration. Results: Talar-declination (43°±8° vs. 30°±8°, p<0.001) and calcaneal-inclination angle (6°±10° vs. 18°±6°, p<0.001) improved significantly, comparably in both groups (p=0.183/p=0.393). No significant differences were observed for fusion-rates (75% vs. 64%; p=0.604) or time-to-fusion (15±7 vs. 11±4 weeks; p=0.285). Major complications occurred in 63% of open and 36% of arthroscopic TTCA. For open TTCA, 80% were SSI necessitating multiple revision-surgeries including one below-the-knee-amputation, for arthroscopic TTCA these were solely non-unions. Comparing patients with ulceration to those without, no relevant change in major SSI in open TTCA (67% vs. 60%) could be detected but a pronounced difference in non-union-rates for arthroscopic TTCA (75% vs. 20%). In patients without ulceration the union-rate was 80% for both, open and arthroscopic TTCA. Conclusion: Taken together, arthroscopic TTCA drastically reduced major surgical side infections compared to open TTCA in high risk patients. In patients without preexisting ulceration excellent union-rates (80%) for both, open and arthroscopic TTCA could be achieved.